Possible modes of transmission of Novel coronavirus SARS-CoV-2: a review - Mukhra, Richa; Krishan, Kewal; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2020)
Abstract: Introduction: The widespread outbreak of the novel SARS-CoV-2 has raised numerous questions about the origin and transmission of the virus. Knowledge about the mode of transmission as well as assessing the effectiveness of the preventive measures would aid in containing the outbreak of the coronavirus. Presently, respiratory droplets, physical contact and aerosols/air-borne have been reported as the modes of SARS-CoV-2 transmission of the virus. Besides, some of the other possible modes of transmission are being explored by the researchers, with some studies suggesting the viral spread through fecal-oral, conjunctival secretions, flatulence (farts), sexual and vertical transmission from mother to the fetus, and through asymptomatic carriers, etc. Aim: The primary objective was to review the present understanding and knowledge about the transmission of SARS-CoV-2 and also to suggest recommendations in containing and preventing the novel coronavirus. Methods: A review of possible modes of transmission of the novel SARS-CoV-2 was conducted based on the reports and articles available in PubMed and ScienceDirect.com that were searched using keywords, ‘transmission’, ‘modes of transmission’, ‘SARS-CoV-2’, ‘novel coronavirus’, and ‘COVID-19’. Articles referring to air-borne, conjunctiva, fecal-oral, maternal-fetal, flatulence (farts), and breast milk transmission were included, while the remaining were excluded. Result and Conclusion: The modes of transmission linked to SARS-CoV-2 were identified and the available literature on each of these is described in detail in view of the possibilities of viral transmission through various modes of transmission. The review provides updated and necessary information on the possible modes of transmission for the health care workers and the lay public under one umbrella that can also be considered during framing guidelines in order to prevent and control the viral spread.